(3GdcdjGJs - (3GdMSjfj GdbQjej Gdcahj, CHhGdHbGA,J (B1095 (3g` s
(3ChdgG (B:s
(3NjQ efWhb Hg CeGe cd ebGd , hGaVd eUOQ Hg cd cJGH ai cd MGd , ebOeI JfRjd GdbQBf , hBNQ OYhi ScGf efGRd GdLfGf JCdja Ldjd bO LeYJ ajg eG ai JUGfja GdCSdGa ef GdbhGYO dVHW eG ajgG ef GdahGFO , efbhdI HCbUQ YHGQI s
(3BNQgG (B:s
(3EdG Cfg ef cJGH GdeTGjN Cfge dGjPcQhf GdeSJfO hjcJahf HGdETGQI Edi GdeYfi GdeDKQ CfJUGQkG hEYJbGOkG Ydi TgQI GdeSJfO ajeG Hjfge GdMeO ddg Ydi fYe GdEdeGe QVhGf Gddg JYGdi Ydjge CLeYjf s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3cJHJ GdeOGNd HGdeOGO GdCMeQ s
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdadSaI hGdefWbs